DIVIDEND POLICY AND CORPORATE PERFORMANCE OF NIGERIAN FIRMS - JEREMIAH BABAJIDE OPALEKE (International Studies Journal)
Managing corporate dividend had forever being a fragile task that requires understanding and consideration of the managerial and business growth variables that are attached to it. This study examined the relationship between corporate dividend policy and the corporate performance of Nigerian manufacturing firms, via three of the literature posited corporate performance indicators: Firm’s Profitability, Investments, and Earnings-per-Share, which existing related studies had ignored. The study was built on Ross and Mitnick’s 1973 and 1975 Agency theory of corporate behaviour. It is a quantitative research design that x-rays a sectoral population of about 173 NSE’s listed Nigerian manufacturing companies, from which twenty-five (25) stratifiedly selected manufacturing samples were tested, covering a period of 10 years (i.e., 2014 to 2024). Two of the dividend theories (Irrelevance and Flow-of-funds) were empirically verified in quest to ascertain their relevance and position. Data gathered were empirically analyzed using, Econometric and Multiple-regression technique, coupled with the t-test reliability mechanisms. The study in its contribution to the wealth of knowledge, established in contrast to most existing related studies that significant positive relationship exists among a firm’s dividend policy, its corporate investments, profitability, and earnings-per-share: the tested indicators of firm’ corporate performance. And it is on the basis of these revelations that the study recommends to the managers of manufacturing companies in Nigeria, to adopt much flexible dividend policy pattern that is educative and communicative enough, to assist them, motivate and convince corporate investors towards prioritizing the need for re-investment of their dividend yields over immediate cash-out in their contribution towards aiding improved corporate performances and desired growth.